Studies on estimation of service per conception rate in Sahiwal breeding bulls - Naha, Binoy (Indian Journal of Dairy Science, 2016)
In the present investigation, studies on conception rate of Sahiwal breeding bulls were considered. The study was conducted on records of 43 Sahiwal bulls maintained under 8 sets of Sahiwal breeding project at ICAR-National Dairy Research Institute, Karnal (India). The data on conception rate of Sahiwal bulls during 27 years (1987-2013) were collected for the study of bull fertility. The study revealed that the average conception rate based on first, second, third and overall AI in Sahiwal bulls were 45.95 ± 1.37, 47.17 ± 1.59, 55.91 ±1.76 and 46.38 ± 1.55%,respectively with the coefficient of variation of 21.84 , 22.01, 22.74 and 22.32%, respectively. It has shown that the average conception rate for first AI was lower as compare to second, third and overall AI. Overall conception rate of heifers (50.17 ±1.62) was higher as compare to adult (44.68 ± 1.31) which may be due to fact that heifers are mostly free from reproductives diseases and non-heifers (adult) are more prone to reproductive diseases.